FAKTOR ANTROPOMETRI YANG BERPENGARUH TERHADAP ATENSI MENGGUNAKAN TES VIGILANCE PADA ANAK USIA 1012 TAHUN DI SDN GARUDA KOTA BANDUNG - Waya Nurruhyuliawati, Siti Aminah, Uni Gamayani, Eddy Fadlyana (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION MALNUTRITION AMONG SCHOOLAGE CHILDREN MAY MANIFEST IN DISORDERS OF GROWTH AND IS ALSO ASSOCIATED WITH POOR LEARNING OUTCOMES NUTRITIONAL BALANCE IS NECESSARY FOR ATTENTION WHICH IS THE BASIS FOR THE DEVELOPMENT OF COGNITIVE FUNCTION AND BEHAVIOR OF INDIVIDUALS